Analisis Kemampuan Guru Mata Pelajaran Pendidikan Agama Islam (PAI) dalam Pengembangan Media Pembelajaran Berbasis Information and Communication Technology (ICT) di SMA Unggul Al-Azhar Medan - Syukri, Ahmad; Septian, Yudhi; Frarera, Andre Nova; Sya’bana, Dzul Fadli; Halimah, Siti (Jurnal Dirosah Islamiyah, 2024)
Anything that may be utilized to communicate ideas or information throughout the teaching and learning process in order to pique students' interest in learning is considered learning media. The purpose of this essay is to examine how Islamic Religious Education (PAI) subject instructors at Unggul Al-Azhar High School in Medan employ ICT-based learning resources. This writing's creation makes use of analytical techniques based on quantitative research and relies on relevant reference materials to delve further into research projects. Based on this study, it was determined that the usage of Information and Communication Technology (ICT) is a factor that effects students' learning accomplishment when it comes to comprehending Islamic religious education in schools in the modern day. Keywords: Information and Communication Technology (ICT), Teacher Ability, instructional Media